Rancang Bangun Sistem Informasi Donor Darah Pada UTD-PMI Kabupaten Sumbawa Berbasis Web App - Imanura Bagaskara, Kukuh; Esabella, Shinta (Buletin Ilmiah Informatika Teknologi, 2025)
The rapid advancement of technology has had a significant impact on the healthcare sector, including blood donor management. The Blood Transfusion Unit (UTD) of the Indonesian Red Cross (PMI) in Sumbawa Regency still relies on a manual system, such as paper forms and WhatsApp communication, leading to long queues, data errors, and delays in donor management. This study aims to design and implement a web-based information system utilizing Progressive Web App (PWA) technology to enhance the efficiency of blood donor registration and data management. The system enables donors and administrators to access and manage data in real time via web and mobile devices. This research employs a qualitative method with an iterative and Agile approach in software development. Testing results indicate that the developed system can accelerate the registration process, reduce queues, and minimize data errors. The implementation of this system is expected to improve the operational efficiency of the UTD-PMI in Sumbawa Regency and support a more responsive and accurate blood supply to meet medical needs.